The Meaning of Kidung Rawapening in Larung Sesaji Ritual at Semarang Regency - Nafik Salafiyah (Journal of Music Science, Technology, and Industry, 2020)
Purpose: The purpose of this study was to find out the meaning of Kidung Rawapening lyrics, the reason why Kidung Rawapening was not accepted by the Muhammadiyah community, and the perspective of NU and Muhammadiyah about Kidung Rawapening. Research Methods: The method used in this research is qualitative with a case study approach, employing Ferdinand de Saussure's semiotic theory to analyze the data. Results and discussion: Research of Kidung Rawapening shows the meaning of gratitude to God for the fortune of Rawapening and gratitude to the ancestors who protected it. Kidung Rawapening makes a viewpoint comparison between Nahdlatul Ulama (NU) and Muhammadiyah. Implication: NU as a community organization believes that praying for ancestors in Kidung Rawapening will be easily answered by God. While Muhammadiyah states that ancestors should not be included in prayer, because such actions are syirik (shirk) and takhayul (superstition).